A cross-cultural analysis of hutong tourism at Nanluoguxiang, Beijing, China: comparison between Beijing, other Chinese and international visitors. (25th July 2019) - Su, Ming Ming; Wall, Geoffrey
Hutongs, a representative street layout with traditional houses of ordinary Beijing residents, have increasingly used as cultural tourism attractions. The role of cultural distance in co-creating such heritage experience for tourists from different backgrounds is important. Taking a cross-cultural perspective, this study compares use patterns, motivations, perceptions and evaluations of Beijing, other domestic and international visitors at Nanluoguxiang hutong tourism site in Beijing through onsite questionnaire surveys. Research indicates that most visitors are young and well educated. Perceptions of the authenticity of the experience decreases and recognition of Nanluoguxiang's representation of Beijing character increases with cultural distance. Activities, such as visiting hutong and interacting with hutong residents, have a stronger influence on perceptions and evaluations of tourists with a greater cultural distance from the host culture. Results support the important role that cultural distance plays in shaping visitor perceptions and evaluations of heritage tourism sites. Practical implications are discussed to inform planning and management of hutong tourism in Beijing.